(untitled) (Fiep Bulletin - online, 2013)
the identification of the potential of the risk factor for a pregnant woman and its concept is the primordial fact in the serch for the reduction of the mather’s fetu’s and neonatal child’s morbidity and mortality index. Aim: assessing risk factors for pregnancy, focusing on prematurity and low birth weight using data of the Brazilian Live Born Information System (SINASC in Portuguese) in the city of Espírito Santo do Pinhal, from 2001 to 2003. Methods: information on maternal age, education, occupation, address, and number of previous pregnancies, length of current pregnancy, kind of delivery, number of prenatal follow-up attendances, date and weight of birth were collected from dataset . The prevalence of each outcomes was estimated and the odds ratios for potential risk factor were estimated using logistic regressions. Results: there was a low percentage of missed information. During the period of study, the prevalence of prematurity, low birth weight, and congenital malformation were 7.7%, 8.6%, and 1.4%, respectively. The spatial distribution was inversely proportional to the socioeconomic status of the analyzed areas. Among the studied risk factors, inadequate prenatal follow up (OR 4.2; IC 95% 2.4-7.2) and extenuating maternal occupation (RC 4.6; IC 95% 1.3-16.3) were the most relevant for prematurity while for low birth weight, the main risk factors were low maternal education (less than eight years) (OR 1.5; IC 95% 1.1-2.2) and inadequate prenatal follow up (RC 2.7; IC 95% 1.6-4.5). Conclusions: It is possible to conclude that SINASC data from Espírito Santo do Pinhal have high quality and are adequate to epidemiological research.